2020
DOI: 10.1038/s41893-020-00622-1
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of interventions for crop postharvest loss reduction in sub-Saharan Africa and South Asia

Abstract: Reducing postharvest losses (PHLs) of food crops is a critical component of sustainably increasing agricultural productivity. Many PHL reduction interventions have been tested, but synthesized information to support evidence-based investments and policy is scarce. In this study, PHL reduction interventions for 22 crops across 57 countries in sub-Saharan Africa and South Asia from the 1970s to 2019 were systematically reviewed. Screening of the 12,907 studies identified resulted in a collection of 334 studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
73
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(76 citation statements)
references
References 43 publications
0
73
0
3
Order By: Relevance
“…Multi-stakeholder testing can be easily combined with training on the proper use of the technologies, and possibly increase their uptake and adoption. Recent evidence synthesis of small-scale farmer postharvest loss reduction technologies in SSA and South Asia revealed that there are very few studies which involve the end-users in the testing of the technologies, or conduct multi-site or multi-year comparisons of the interventions 10 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multi-stakeholder testing can be easily combined with training on the proper use of the technologies, and possibly increase their uptake and adoption. Recent evidence synthesis of small-scale farmer postharvest loss reduction technologies in SSA and South Asia revealed that there are very few studies which involve the end-users in the testing of the technologies, or conduct multi-site or multi-year comparisons of the interventions 10 .…”
Section: Discussionmentioning
confidence: 99%
“…This translates to over 9,400 tonnes in 2018 with a monetary value of approximately US$3.7 million using Zimbabwe Grain Marketing Board prices. There has been limited efforts to address these sorghum postharvest losses in Africa 9 , 10 . Practical postharvest grain storage options need to be developed to complement existing crop production efforts to achieve food and nutrition security.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the country produces 240 million tons of food, of which 15 to 25 million tons are wasted annually, and this loss is sufficient to meet the food needs of 0.1 billion people. These losses usually occur during harvesting, threshing, drying, storage, transport, processing, and marketing (Stathers et al, 2020;Kalita, 2017 andLundqvist et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…At the fourth stage, four hundred farming households were selected through a proportionate sampling technique. Finally, (50,46,43,37,29,30,39,42,22,17,24,21) farming household from each village were selected through proportionate. Data analysis was carried out by using descriptive as well as inferential statistics.…”
Section: Universe and Sampling (Quantitative Data)mentioning
confidence: 99%
“…from the Ceres2030 team's findings includes the striking statement that "most of the included studies only involved researchers without any participation from farmers" 5 .…”
mentioning
confidence: 99%